THE IMPACT OF CORPORATE GOVERNANCE STRUCTURE ON THE QUALITY OF FINANCIAL REPORTING - Jahan Gylyjova (Modern American Journals, 2025)
This article examines the impact of key elements of corporate governance structure (board composition, audit committee independence and competence, CEO/chairman separation, ownership concentration, and institutional investors) on financial reporting quality. Drawing on agency theory and a review of empirical research, this article analyzes the mechanisms through which corporate governance influences management's propensity to manipulate earnings, the completeness and reliability of disclosures, and the likelihood of financial fraud. A synthesis of empirical evidence and practical recommendations for regulators and corporate boards are presented.
Keywords: corporate governance, financial reporting quality, earnings management, board of directors, audit committee, ownership structure.